Terrorism, Tourism and the End of Hospitality in the 'West' - Korstanje, Maximiliano E. (Springer International Publishing, 2018)
This book explores how the contemporary threat of terrorism is eroding the concept of hospitality in the West. Going beyond the immediate effects of terrorism that are daily portrayed in the media and have shaped the foreign policy agenda of politicians in Europe and the US, this study explores the conceptual framework of how terrorism emerged and expanded within the West and shows how it interacts with, and targets, leisure consumerism and the international hospitality industry.